SMALL HYDROELECTRIC POWER PLANTS IN AGRICULTURE - Azizulloh Torajonov (Лучшие интеллектуальные исследования, 2024)
Abstract: The integration of small-scale hydroelectric power plants in the agricultural sector has significant implications for sustainable energy production and efficient water management. This study explores the potential of small hydroelectric power stations to provide renewable energy to agricultural operations while also managing water resources for irrigation and other agricultural needs. The research examines the design, implementation, and operation of small hydro plants within the context of agriculture, focusing on capacity planning, site selection, environmental considerations, and the synergy between water and energy needs. By employing case studies and quantitative analyses, the study highlights the benefits of small hydroelectric facilities, such as reduced carbon footprint, decreased reliance on fossil fuels, diversification of energy sources, and enhanced water use efficiency. It also addresses the challenges faced by these installations, including ecological impacts, initial capital costs, regulatory frameworks, and technical expertise requirements.